“KATAMIAˮ (Kader Tangani Anemia) dalam Upaya Penanganan Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Dirgahayu - Satsiwi Wahyu Widi Handayani; Rena Herlena; Fadhiyah Noor Anisa; Istiqamah Istiqamah (Jurnal Pengabdian Bidang Kesehatan, 2024)
Prevention of anemia in pregnant women can be done with appropriate health behavior. Health behaviors such as maintaining a diet high in iron, regularly consuming iron tablets, and carrying out ANC during early pregnancy can reduce the prevalence of anemia in pregnant women. Diet is an important factor that pregnant women must pay attention to. Poster media is one media that has a lot of information about the diversity of foods that are useful for preventing anemia and can be used to help carry out health education. Create "KATAMIA" (Cadres Handle Anemia) so that anemia in pregnant women becomes a global problem that has an impact on the mother and fetus. Community service activities through cadres by providing education to cadres about Fe tablet information which is carried out in the form of health education and providing "KATAMIA" (Cadres Handle Anemia) Posters to Pregnant Women in the Gunung Sari Village Area. As a result of the activity, the "KATAMIA" innovation has been implemented as an effort to reduce the incidence of anemia in pregnant women in Gunung Sari Village. "KATAMIA" which is carried out by female students is expected to be able to contribute to the cadres as an effort to increase compliance in taking Blood Additive Tablets among pregnant women and can also increase the motivation of pregnant women to take Fe Tablets according to their achievements